Chemical Stimulants and Stressors Impact the Outcome of Virus Infection and Immune Gene Expression in Honey Bees (Apis mellifera) - Parekh, Fenali; Daughenbaugh, Katie F.; Flenniken, Michelle L. (Frontiers in Immunology, 2021)
Western honey bees (Apis mellifera) are ecologically, agriculturally, and economically important plant pollinators. High average annual losses of honey bee colonies in the US have been partially attributed to agrochemical exposure and virus infections. To examine the potential negative synergistic impacts of agrochemical exposure and virus infection, as well as the potential promise of phytochemicals to ameliorate the impact of pathogenic infections on honey bees, we infected bees with a panel of viruses (i.e., Flock House virus, deformed wing virus, or Sindbis virus) and exposed to one of three chemical compounds. Specifically, honey bees were fed sucrose syrup containing: (1) thyme oil, a phytochemical and putative immune stimulant, (2) fumagillin, a beekeeper applied fungicide, or (3) clothianidin, a grower-applied insecticide. We determined that virus abundance was lower in honey bees fed 0.16 ppm thyme oil augmented sucrose syrup, compared to bees fed sucrose syrup alone. Parallel analysis of honey bee gene expression revealed that honey bees fed thyme oil augmented sucrose syrup had higher expression of key RNAi genes (argonaute-2 and dicer-like), antimicrobial peptide expressing genes (abaecin and hymenoptaecin), and vitellogenin, a putative honey bee health and age indicator, compared to bees fed only sucrose syrup. Virus abundance was higher in bees fed fumagillin (25 ppm or 75 ppm) or 1 ppb clothianidin containing sucrose syrup relative to levels in bees fed only sucrose syrup. Whereas, honey bees fed 10 ppb clothianidin dose had lower virus levels, likely because consuming a near lethal dose of insecticide made them poor hosts for virus infection. The negative impact of fumagillin and clothianidin on honey bee health was indicated by the lower expression of argonaute-2, dicer-like, abaecin, and hymenoptaecin, and vitellogenin. Together, these results indicate that chemical stimulants and stressors impact the outcome of virus infection and immune gene expression in honey bees.